2000
DOI: 10.1207/s15327078in0103_4
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Infants' Attention: The Interactive Influence of Attentional State and Stimulus Characteristics

Abstract: The interactive effects of stimulus characteristics and attentional state on infants' distraction latency were studied. As 7-month-old infants explored initial stimuli that were composed of either a single nonmoving component or multiple moving components, one of several types of distractors was presented in the periphery. Infants' distraction latencies (the amount of time they took to turn from the initial stimulus to the distractor) vaned as a hnction of the interaction between the infants' attentional state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 20 publications
5
26
1
Order By: Relevance
“…This finding confirms that the present data are similar to data obtained in previous studies using this same procedure. Indeed, the mean latencies reported here are similar to those reported in previous investigations (Oakes & Tellinghuisen, 1994;Oakes et al, 2000;Tellinghuisen & Oakes, 1997;Tellinghuisen et al, 1999).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding confirms that the present data are similar to data obtained in previous studies using this same procedure. Indeed, the mean latencies reported here are similar to those reported in previous investigations (Oakes & Tellinghuisen, 1994;Oakes et al, 2000;Tellinghuisen & Oakes, 1997;Tellinghuisen et al, 1999).…”
Section: Resultssupporting
confidence: 91%
“…Tellinghuisen, Oakes, and Tjebkes (1999), for example, found that when 7-monthold infants were in a focused or concentrated attentional state, distractors needed to be more salient to cause a reorientation of attention than when infants were in a more casual attentional state. Similarly, Oakes, Tellinghuisen, and Tjebkes (2000) reported that 7-month-old infants were least distractible when they were engaged in focused attention toward a complex initial target. Thus, attention allocation in infancy appears to be jointly determined by endogenous and exogenous factors.…”
Section: Introductionmentioning
confidence: 92%
“…In particular, the data suggest that children habituated more readily to a periodic distractor (intermittent distraction condition) than to a continuous (continuous distraction condition) one. This decrease in looking to the intermittent distractor over time is consistent with other research using intermittent distractors (e.g., Hale & Flaugher, 1977;Oakes et al, 2000Oakes et al, , 2004Tellinghuisen & Oakes, 1997), and it might account for the persistent effects of continuous distraction seen here well into the preschool period.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the characteristics of the distractor (e.g., auditory and visual components, complexity) have been shown to affect distractibility in infants (e.g., Oakes, Tellinghuisen, & Tjebkes, 2000;Ruff & Capozzoli, 2003;Tellinghuisen, Oakes, & Tjebkes, 1999). In contrast, there is little systematic investigation of the effects of distractor characteristics on distractibility and performance during the toddler and preschool years.…”
Section: Kannass and Colombomentioning
confidence: 99%
See 1 more Smart Citation